Pembentukan Citra diri Pinilih Jajaka Kabupaten Bandung 2019 - Abbad Bani Adam; Neni Yulianita (UNISBA Press, 2022)
Abstract. Jajaka is the embodiment of the superior young generation who will later become an example for other young generations, especially in the fields of culture and tourism. Therefore, a jajaka must be smart in attitude, which means that a jajaka must be able to position himself when he is in front of the public and also when speaking behind the public. But in fact a jajaka is also an ordinary human who has different characteristics and characters. This research is entitled